PENINGKATAN KETERAMPILAN SOSIALMELALUI METODE BERMAIN PERAN - Pujiati, Desti (Dinamika, 2015)
Abstract. This study aims to improve the social skills of children through the method of role playing in the kindergarten Muhammadiyah University of Purwokertoâs Labschool and to determine the constraints of social skills through role play methods which are given to children.The research method used was action research method. This study was conducted from 4 March to 20 May 2013.. The analysis method of research using qualitative and quantitative approaches. The success of the research is concluded with the analysis using the percentage. Research declared successful if the percentage of social skills assessment> 40 after doing activities with role playing method.In the second cycle, twenty studentshas increased social skills. Highest percentage increase in social skills achieved by the subject Yz, at 96.6%.Roleplaying learning methods thatimplemented by teachers with step (1) propose and discuss the situation. (2) prepare a roleplaying, (3) playing (4) reveals the experience ; have done well. The objectives of the research has achieved with the maximum expected.KeywordsÂ Â Â Â Â Â  :Â Â Â Â Â Â Â Â Â Â  Skiil social, role play method, action research